RANCANG BANGUNMEDIA INFORMASI TENTANG TRADISI ABA-ABAAN DALAM BENTUK FILM DOKUMENTERMENGGUNAKANADOBE PREMIERE CC 2017 - Ni Kadek Ariasih; Ida Bagus Guna Bhiksana Manuaba (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTThis study examines three important aspects of the Aba-Abaan tradition, namely economic, social, and cultural. Changes in the traditional system of ignorance will affect all three aspects. From the results of observations that have been made, it shows that there is a shift in the means of an ignorance tradition that was originally in the form of staple food into an envelope and a lack of understanding of the meaning the aba-abaan tradition. Based on the problems that occur, where the community needs alternative media to provide information about the aba-abaan tradition which is more interesting, easy to understand, and provides education on the good and bad effects of the aba-abaan tradition if the tradition starts to be forgotten. From these problems, documentary films were chosen as media to provide information and education that are interesting and easily understood by the public. The results of this study indicate that the power of tradition can sustain the economic, social and cultural systems of society.Keywords: Aba-abaan Traditions, Documentary Films.ABSTRAKPenelitian ini mengkaji tiga aspek penting dalam tradisi Aba-abaan, yaitu ekonomi, sosial dan budaya. Perubahan sistem tradisi aba-abaan akan mempengaruhi ketiga aspek tersebut. Dari hasil observasi yang telah dilakukan, menunjukan bahwa terjadinya pergeseran sarana tradisi aba-abaan yang awalnya berupa bahan makanan pokok menjadi amplop, dan kurangnya pemahaman tentang makna dari tradisi aba- abaan. Berdasarkan masalah yang terjadi, dimana masyarakat membutuhkan media alternatif untuk memberikan informasi tentang tradisi aba-abaan yang mudah dipahami serta memberikan edukasi pada dampak baik dan buruk tradisi aba-abaan jika tradisi tersebut mulai terlupakan. Dari permasalahan tersebut, film dokumenter dipilih sebagai media untuk memberikan informasi dan edukasi yang menarik dan mudah dipahami oleh masyarakat. Hasil penelitian ini menunjukan bahwa kekuatan tradisi dapat menopang sistem perekonomian, sosial dan budaya masyarakat.Kata Kunci : Tradisi Aba-abaan, Film Dokumenter.